Quantification of lactate from various metabolic pathways and quantification issues of lactate isotopologues and isotopmers - Wei Zhang (Nature Portfolio, 2017)
Abstract 13C-labeled glucose combined with chromatography and mass spectrometry enables us to decipher the percentage of lactate generated from various metabolic pathways. We showed that lactate derived from glycolysis, pentose phosphate pathway, Krebs cycle, and other sources accounted for 82–90%, 6.0–11%, 0.67–1.8% and 1.5–7.9%, respectively, depending on different types of cells. When using glucose isotopomers ([1-13C]-, [3-13C]-, [4-13C]-, and [6-13C]glucose) or isotopologues ([1,2-13C2]- and [1,2,3-13C3]glucose) for tracing, the ratio of lactate derived from glucose carbon 1, 2, 3 over 4, 5, 6 via glycolysis varied significantly, ranging from 1.6 (traced with [1,2-13C2]glucose) to 0.85 (traced with [6-13C]glucose), but the theoretical ratio should be 1. The odd results might be caused by intramolecular 13C, which may significantly affect lactate fragmentation under tandem mass spectrometry condition, leading to erroneous quantification. Indeed, the fragmentation efficiency of [U-13C]lactate, [2,3-13C]lactate, and [3-13C]lactate were 1.4, 1.5 and 1.2 folds higher than lactate, respectively, but [1-13C]lactate was similar to lactate, suggesting that carbon-13 at different positions could differentially influence lactate fragmentation. This observed phenomenon was inconsistent with the data based on theoretical calculation, according to which activation energies for all lactate isotopomers and isotopologues are nearly identical. The inconsistency suggested a need for further investigation. Our study suggests that calibration is required for quantifying metabolite isotopolugues and isotopomers.